The use of copulas in spread trading - Liew, Rong Qi (2013)
Spread trading is the simultaneous sale of one security and the purchase of a related security. One who is involved in spread trading will desire to have an ideal entry point into and exit point out of the market using the technique which is developed based on the dependence of the two securities. It is widely acknowledged that stock prices are rarely normally distributed in reality. Yet most people are still using linear correlation as a measure of dependency due to the lack of alternatives. As copula methodology emerge in the recent decade, many suggest copula as an alternative to normality. The use of copulas is essential but relatively new to the spread trading. The copula methodology captures non-linear dependencies, making the model robust and this leads to an outcome that is more superior, and therefore better decision. The objective of this study is to develop an equity trading technique for spread trading by using the emerging copula methodology. [1st Award]